Pengaruh Serbuk Batu Kapur terhadap Karakteristik Beton - Nurul (Retii, 2019)
The use of concrete for construction materials is currently very large, so the demand for cement is also getting bigger, consequently the price of cement is more expensive. In order to reduce the use of cement, variations in cement were tried with limestone powder, where the limestone powder contained silica, calcium carbonate, aluminum and magnesia similar to the constituent of cement. In this study the use of limestone powder in proportion with cement. It is hoped that the optimal characteristic results (density and slump) will be obtained from the proportion of cement with the limestone powder. The study made the proportion of limestone powder of 0%, 5%, 10%, 15% and 20% of cement. The results obtained are based on the optimal characteristics of the proportion of cement and limestone powder that is in the proportion of 10%. Keywords: Concrete, limestone powder, cement and slump.